Theoretical approaches to the formation and development of human capital - Zemtsov, A.A.; Gartsueva, E.V. (Ye.A.Buketov Karaganda State University Publishing house, 2016)
At the present stage of development of the national economy a human capital plays an important role. Without involving it the transition to an innovative path of development is impossible. Thanks to the development of human capital, a competitiveness and economic growth, production efficiency can be increased. The article is devoted to theoretical approaches to the definition of human capital. The article is based on a method of comparative analysis. The authors have analyzed different definitions of human capital and summarized the views of the researchers in this field. The basic approaches reflecting the contents of the examined category are singled out.
Адами капитал концепциясының құрылуы мен дамуының теориялық тəсілдемесі
Теоретические подходы к становлению и развитию концепции человеческого капитала
Keywords: capital; human capital; human capital theory